2021
DOI: 10.5334/gh.945
|View full text |Cite
|
Sign up to set email alerts
|

24-h-Ambulatory Blood Pressure Monitoring in Sub-Saharan Africa: Hypertension Phenotypes and Dipping Patterns in Malawian HIV+ Patients on Antiretroviral Therapy

Abstract: Background: Cardiovascular disease and especially hypertension are a growing problem among people living with HIV (PLHIV) on antiretroviral therapy (ART) in sub-Saharan Africa. Objectives: As robust data on hypertension phenotypes associated with distinct cardiovascular risks among PLHIV are limited, we aimed to assess the frequency of white-coat (WCH), masked (MH) hypertension, and blood pressure dipping-patterns in a group of Malawian PLHIV. Methods: As part of the prospective Lighthouse-Tenofovir-Cohort-Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
1
1
0
1
Order By: Relevance
“…48 The few studies that have explored the profiles of nocturnal blood pressure (BP) dipping among individuals living with HIV (PLHIV) in Sub-Saharan Africa (SSA) support our finding of a high prevalence of non-dipping systolic BP among PLHIV. 49,50,51 Our observation of a prevalent non-dipping BP profile during the night among both PLHIV and PwoHIV closely aligns with recent research conducted by Nolan et al in Tanzania. 51 However, in contrast to our findings, Nolan et al reported a higher, albeit statistically insignificant, prevalence of non-dipping nocturnal BP among PLHIV compared to PwoHIV (64.2% [36/56] versus 53.1% [43/81]).…”
Section: Discussionsupporting
confidence: 90%
“…48 The few studies that have explored the profiles of nocturnal blood pressure (BP) dipping among individuals living with HIV (PLHIV) in Sub-Saharan Africa (SSA) support our finding of a high prevalence of non-dipping systolic BP among PLHIV. 49,50,51 Our observation of a prevalent non-dipping BP profile during the night among both PLHIV and PwoHIV closely aligns with recent research conducted by Nolan et al in Tanzania. 51 However, in contrast to our findings, Nolan et al reported a higher, albeit statistically insignificant, prevalence of non-dipping nocturnal BP among PLHIV compared to PwoHIV (64.2% [36/56] versus 53.1% [43/81]).…”
Section: Discussionsupporting
confidence: 90%
“…24-h ambulatory BP monitoring (24-h-ABPM) was not available when recruitment for the LighTen Study started. However, when 24-h-ABPM was performed in a subgroup of 117 LighTen participants, a median of 26 months (6–8 visits) after enrollment, white coat hypertension or white coat effect was identified in 18.8% of those with office hypertension [ 84 ]. Self-reported hypertension could have been another important source of bias and is known to be considerably flawed [ 85 ], but patients without antihypertensive drug treatment and BP values < 140/90 mmHg were not included in the calculation of the prevalence of hypertension.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Além disso, estudos retrospectivos e transversais demonstram que a prevalência de hipertensão é maior em adultos infectados pelo HIV quando comparados aos não infectados (BATAVIA et al, 2018;CUNHA et al, 2018;KASPER et al, 2021). A Pressão Arterial (PA) elevada é um importante determinante da sobrevida em longo prazo em PVHIV (BATAVIA et al, 2018;BARROSO et al, 2021;KASPER et al, 2021;).…”
Section: Alterações Metabólica Relacionadas à Pressão Arterialunclassified